POLLUTION OF AXIAL AXIS TURBINE TURNING COMPRESSOR SURFACES AND THEIR ENVIRONMENTAL CONSEQUENCES - Карпенко, Сергій Володимирович (Problems of Friction and Wear, 2021)
It was found that the contamination of the surfaces of axial compressors of gas turbines and their impact on the environment is an urgent task of the general problem of pollution by harmful substances in the environment. The main source of air pollution is dust, as well as various pollutants emitted by gas turbine units. The granulometric characteristics of dust and its composition are given. It has been established that dust from atmospheric air also leads to erosion of axial compressor blades, which has a negative impact on the environment, as well as two ways of influencing erosion processes. The atmosphere of the air used for the operation of gas turbines always includes a number of solid and liquid particles of pollution. Their concentration in the air depends on environmental conditions, increases sharply due to dust and sandstorms, emissions from enterprises, and so on. The main source of air pollution is dust. The open surface of the soil is the main source of natural dust, and wind is the main factor in its spread. The concentration of dust is proportional to the wind speed in the cube. It is shown that dust collectors are most effective for protection of gas turbine units from dust of atmospheric air, saturated mostly with elastic particles of pollution. A system of differential equations for the relative motion of a dust particle in a dust collector lattice is compiled and solved. Factors that reduce the performance of gas turbines due to pollution and increase the negative impact on the environment are identified. The developed methods and techniques allow to estimate the level of pollution of the blades of axial compressors of gas turbines and their negative impact on the environment. The classification of pollution of blades of axial compressors of gas turbine installations is offered.